Rancang Bangun Aplikasi Arsip Surat Menyurat Elektronik Dengan Model Agile Pada Kantor Desa Setia Karya Mandailing Natal - Febrianda Lubis; Eko Hariyanto; Rio Septian Hardinata (Bulletin of Information Technology (BIT), 2023)
One of the most influential sources of information is administration. Recording or storage of administrative files is commonly called archives. Recording or storage of administrative files is commonly called archives. The condition that is being carried out at the Setia Karya Village Office in terms of managing correspondence archives is still using a manual method. The data collection of incoming and outgoing mail is recorded in a book as a record of its data collection and archives are stored in filing cabinets. The data collection of incoming and outgoing letters also has separate books for incoming and outgoing letters and is stored in a storage cupboard. The application design in this study that the authors use is the Agile model, which is an approach to analyzing and designing systems that are developed through the use of more specific cycles for the activities carried out. The diagrams used are Data Flow Diagrams (DFD), flowcharts, and Entity Relationship Diagrams (ERD). The results of the design and testing that has been carried out by the author on this system indicate that the functions contained in the application are running well and in accordance with the needs and design, can manage incoming and outgoing letters such as the process of managing letters in the Setia Karya Village Office, and can provide convenience to the Admin in processing and processing archived correspondence